The Role of Scientific Research in Local Community Service from the Perspective of Faculty Members of some Palestinian Universities - Zeiad Barakat (University of Science and Technology, Yemen, 2020)
The present study aimed at investigating the role of scientific research in the development of the local community from the point of view of the faculty members in the Palestinian Universities. To achieve this objective, a convenient sample of (244) faculty members from the universities of northern Palestine: Al-Quds Open University (Tulkarm), An-Najah National (Nablus), Technical Palestine - Khadouri (Tulkarem), and Arab American (Jenin). The results of the study showed that the participants' assessment of the importance of the role of scientific research in community development was medium in the overall instrument and two dimensions: applied research and scientific consultancy, but their assessment of awareness-raising was high. On the other hand, the results showed that there were statistically significant differences in the level of the role of practical research in the development of the community attributed to the gender variable in favor of males on the overall instrument and three dimensions, while there were no statistically significant differences in the level of participants' assessment attributed to the variable of specialization. The differences were in favor of the disciplines of educational sciences and applied sciences. There were also statistically significant differences in the level of their assessment attributed to the qualification variable on the overall instrument and the three dimensions in favor of PhD holders. Keywords: scientific research, community service, awareness-raising, applied research, scientific consultancy.